Guaranteeing employment in rural India during the Covid-19 pandemic - Mishra, Subrat Kumar and Khan, M.D. Firoz (Economic and Political Weekly)
The role of the state in guaranteeing employment in rural areas in the wake of a pandemic-induced lockdown is analysed. The Mahatma Gandhi National Rural Employment Guarantee Scheme, the largest ever public funded programme for wage employment in India, is instrumental in bringing social security in rural areas during the pandemic period. However, the adequacy of employment provided was not at the scale it needed. The problem compounded with income fluctuations and regression of consumption expenditure of rural casual workers during the pandemic.- Reproduced
Keywords: Employment, Rural India, Covid-19 pandemic